DILEMMA OF MAKING MORAL CHOICES IN JOE WRIGHT'S PRIDE AND PREJUDICE(2005): AN EXISTENTIALIST CRITICISM - RACHMAWATI, VIONA EVY (2011)
This study is about dilemma of making moral choices in Pride and Prejudice movie (2005). This objective of the study is to apply the Existentialist Criticism to analyze the dilemma of making moral choices in Pride and Prejudice. This study belongs to qualitative study. In this method, the writer uses two types of data source, namely primary and secondary data source. The primary data source and the object of the study is the movie itself, meanwhile the secondary one is any literature related to this study for example reading some other resources related to the movie. The writer collects the data from both primary and secondary data source in sort of document as evidence. The technique of analyzing data is descriptive. Having analyzed this movie, the writer draws some conclusions as follows. First, based on the structural analysis, the director successfully delivers the moral message through the excellent unity of structural element. The director wants to say that everyone have they own dilemma to decide right choice in life, the best decision is when the decision has good effect not only for himself but for everyone he loved also. Second, based on the Existentialist analysis, Joe Wright describes the internal conflict of a girl. That internal conflict forces her to make a right decision from many choices in her life not only for her future but also everyone she loved.